Design Parameters for Gasification of Maize Cobs in Throatless Gasifier - Chopra, Sangeeta; Jain, A K; Gupta, P K; Singh, A K; Jindal, R K; Singh, P (Journal of Agricultural Engineering, 2008)
The gasification of shelled maize cobs was conducted in throatless gasifiers having 15, 22.5, 30 and 36 cm diameter reactors. The experiments were conducted with varying gas flow rate in such a way that the corresponding variation in specific gasification rate (SGR) was in the range of 120-270 kg.h?¹.m². For each reactor, the best performance was obtained with SGR of 165 kg.h?¹.m-². The combustible gases were observed to be 31-38% of the producer gas at optimum SGR. The lower heating value of producer gas was 4.2-5.22 MJ.Nm?³. Maximum gasification efficiency obtained was 66.8-68.9% at optimum SGR. The average equivalence ratio was 0.47. The effect of diameter of reactor on efficiency of gasification was not significant, whereas the specific gasification rate (SGR) had a significant effect on gasification efficiency. The SGR value of 165 kg.h?¹.m² may be used as design parameter for gasification of maize cobs in throatless gasifier.